Chemotherapy for gastric cancer patients – time for personalization in medicine? - Nowara, Elżbieta; Boratyn-Nowicka, Agnieszka; Polakiewicz-Gilowska, Anna; Drosik, Anna; Kustra, Magdalena; Huszno, Joanna (Contemporary Oncology/Współczesna Onkologia, 2012)
Gastric cancer is one of the most frequent neoplasms. Although the incidence of gastric cancer worldwide has declined, there is still high mortality. Treatment of inoperable disease is under evaluation in clinical trials. In palliative treatment chemotherapy containing cisplatin and 5-fluorouracil is the most widely used. In the past years progress in tumour biology has advanced greatly and has led to development of new molecules aimed at targets important for cancer expansion. There are several randomized trials under targeted therapies for gastric cancer patients. One of them led to approval of trastuzumab. In the current paper the authors illustrate new possibilities in systemic treatment with particular attention to targeted therapy and personalization in medicine.